Where Do We Draw the Line? Interlopers, (Ant)agonists, and an Unbounded Journalistic Field - Eldridge II, Scott A. (2019)
Journalism’s once-neglected periphery has been a focus of academic research in recent years and the urge to make sense of interlopers from the periphery has brought about many approaches to understanding these changes. In this essay I reflect on an ongoing research agenda examining one particular category of interlopers: provocative media actors who have openly challenged the boundaries of the journalistic field. These actors raise questions as to how to account for interlopers at the edges of the journalistic field, including whether we should extend the field to include them. In this essay I argue we should continue to see the field as complex, and maybe now a bit more so. Reflecting on field and practice theories and understandings of boundaries, I reengage the complexity that is a core demand of conceptualizing the journalistic field, while offering ways to consider interlopers’ journalistic identities within its boundaries. Emphasizing similarities over differences, I argue we can move beyond binary distinctions between a field’s core members and interlopers on the periphery by focusing on the nature of interloper work.